Implementation of Tourism Village Policy in South Minahasa Regency - Areros, William A.; Lengkong, Florence D. J.; Londa, Very Y. (Journal of Asian Multicultural Research for Social Sciences Study, 2022)
The tourism sector is currently the leading sector of local governments in an effort to develop their regions. South Minahasa Regency, which is rich in tourism potential, establishes a tourism village policy by taking into account the potential of the village. The tourism village policy is expected in addition to managing tourism objects that are owned through local wisdom as well as in an effort to increase community and regional income. By using a qualitative design, it was found that the implementation of tourism village policies in South Minahasa Regency had not been carried out properly judging from the aspects of policy content, implementing organizations and the policy environment. To be able to make the tourism village policy in South Minahasa Regency well implemented, improvements are needed in the preparation and implementation of tourism infrastructure development programs in the village by the South Minahasa Regency Government, strengthening the potential of rural communities through training in making typical village products to support tourism activities, and involving interest groups. such as tourism actors and the private sector to invest in tourism locations.